Hashtags and retweets: using Twitter to aid Community, Communication and Casual (informal) learning - Peter Reed (Association for Learning Technology, 2013)
Since the evolution of Web 2.0, or the Social Web, the way in which users interact with/on the Internet has seen a massive paradigm shift. Web 2.0 tools and technologies have completely changed the dynamics of the Internet, enabling users to create content; be it text, photographs or video; and furthermore share and collaborate across massive geographic boundaries. As part of this revolution, arguably the most significant tools have been those employing social media. This research project set out to investigate student's attitudes, perceptions and activity toward the use of Twitter in supporting learning and teaching. In so doing, this paper touches on a number of current debates in higher education, such as the role (and perceived rise) of informal learning; and debates around Digital Natives/Immigrants vs. Digital Residents/Visitors. In presenting early research findings, the author considers the 3Cs of Twitter (T3c): Community, Communication and Casual (informal) learning. Data suggests that students cannot be classed as Digital Natives purely on age and suggests a rethinking of categorisations is necessary. Furthermore, the data suggests students are developing their own personal learning environments (PLEs) based on user choice. Those students who voluntarily engaged with Twitter during this study positively evaluated the tool for use within learning and teaching.